Developing sanitation planning options: A tool for systematic consideration of novel technologies and systems. (1st October 2020) - Spuhler, Dorothee; Germann, Verena; Kassa, Kinfe; Ketema, Atekelt Abebe; Sherpa, Anjali Manandhar; Sherpa, Mingma Gyalzen; Maurer, Max; Lüthi, Christoph; Langergraber, Guenter
Abstract: To provide access to sustainable sanitation for the entire world population, novel technologies and systems have been developed. These options are often independent of sewers, water, and energy and therefore promise to be more appropriate for fast-growing urban areas. They also allow for resource recovery and and are adaptable to changing environmental and demographic conditions what makes them more sustainable. More options, however, also enhance planning complexity. Structured decision making (SDM) can help balance opposing interests. Yet, most of the current research focuses on the selection of a preferred option, assuming that a set of appropriate options is available. There is a lack of reproducible methods for the identification of sanitation system planning options that can consider the growing number of available technology and the many possible system configurations. Additionally, there is a lack of data, particularly for novel options, to evaluate the various sustainability criteria for sanitation.To overcome this limitation, we present a novel software supported approach: the SANitation sysTem Alternative GeneratOr ( Santiago ). To be optimally effective, Santiago is required to be integrated into an SDM approach. In this paper, we present all the elements that such an integration requires and illustrate these methods at the case of Arba Minch, a fast growing town in Ethiopia. Based on this example and experiences from other cases, we discuss the lessons learnt and present the advantages potentially brought by Santiago for sanitation planning The integration requires four elements: a set of technologies to be looked at, decision objectives for sustainable sanitation, screening criteria to evalute technology appropriateness, and about the technologies and the casea. The main output is a set of sanitation system options that is locally appropriate, diverse in order to reveal trade-offs, and of a manageable size. To support the definition of decision objectives, we developed a generic objective hierarchy for sustainable sanitation. Because one of the main challenges lies in the quantification of screening criteria, we established the data for 27 criteria and 41 technologies in a library.The case studies showed, that if the integration is successful, then Santiago can provide substantial benefits: (i) it is systematic and reproducible; (ii) it opens up the decision space with novel and potentially more appropriate solutions; (iii) it makes international data accessible for more empirical decision making; (iv) it enables decisions based on strategic objectives in line with the sustainable development goals; (v) it allows to prioritise appropriate and resource efficient systems right from the beginning (vi) and it contributes to a more citywide inclusive approach by bridging strategic objectives with an area-based appropriateness assessment. The here presented approach enables the prioritisation of appropriate and resource efficient sanitation technologies and systems in strategic planning. Thereby this approach contributes to SDG 6.2, 6.3, and 11, sustainable sanitation for all. Graphical abstract: Image 1 Highlights: Santiago software provides locally appropriate sanitation system planning options. The procedure for integrating Santiago into structured decision making is presented. Decision objectives and screening criteria are defined in participatory workshops. International data is matched with local conditions to evaluate appropriateness. Appropriate options for all areas are provided by considering novel technologies.